MALDI-TOF-MS and in-depth dynamic simulations on the molecular forces determining the stability of the 4-hydroxybenzoic acid – β-Casein complex following UHT-like treatment. (30th January 2023) - Condict, Lloyd; Cavallo, Jonathan; Hung, Andrew; Ashton, John; Kasapis, Stefan
Highlights: MALDI-TOFD- MS directly confirmed β -casein-4-hydroxybenzoic acid covalent complexes. A 3D structure of covalently bound β -casein-4-hydroxybenzoic acid was developed. Molecular dynamics simulations indicated changes to solvent accessibility. Altered hydrogen bonding on complexation led to decreased protein structural stability. Abstract: Previous work has suggested the ability of 4-hydroxybenzoic acid (4HBA) to bind to β - casein following ultra high temperature-like processing (UHT) in model aqueous systems. The present work confirmed directly, using MALDI-TOF-MS, the presence of covalently bound 4HBA following UHT-like treatment. In subsequent molecular dynamics simulations, the 3D structure of the β - casein molecule was modified so that the meta -C of 4HBA ring and the side chain amino group of lys32 were linked covalently. Such simulations further indicated that the covalent addition of the phenolic compound had impacted the protein density and solvent accessibility. Hydrogen bond analysis between lys32 and the remainder of the protein structure revealed that the covalent complexation supported the formation of additional hydrogen bonds. These increased from potentially 9, in the single protein molecule, to 51 in the complex with 4HBA. However, the persistence of hydrogen bonds was reduced, leading overall to decreased stability and increased protein flexibility.